Arquitecturas-Imaginadas: Representação Gráfica Arquitectónica e “Outras-Imagens (diségno, 2018)
The seminar Arquitecturas Imaginadas: Representação Gráfica Arquitectónica e ‘Outras Imagens’ – kept in Brazil at the Centro Universitário Maria Antônia of the University of San Paolo from the 5th to the 9th of March 2018, one of the first abroad scientific meetings supported by Unione Italiana per il Disegno – has reached its fifth edition and caught the attention of the scientific representation community (fig. I). The first edition, named Desenho [...] Cidade, was taken at the Architecture Department of the University of Lisbon from the 28th to the 30th of April 2014 during the namesake project started from Pedro António Janeiro in 2009 at the CIAUD Centro de Investigação em Arquitetura Urbanismo e Design of the University of Lisbon and during it the most general aspects regarding the drawing and representation of the city were analysed (read more).